2020
DOI: 10.1002/ana.25891
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Decreases with Metabolic Stress in Sickle Cell Disease

Abstract: Objective: Children with sickle cell disease (SCD) experience cognitive deficits even when unaffected by stroke. Using functional connectivity magnetic resonance imaging (MRI) as a potential biomarker of cognitive function, we tested our hypothesis that children with SCD would have decreased functional connectivity, and that children experiencing the greatest metabolic stress, indicated by elevated oxygen extraction fraction, would have the lowest connectivity. Methods: We prospectively obtained brain MRIs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
(204 reference statements)
1
11
0
Order By: Relevance
“…We postulate that OEF may risk stratify microstructural impairment prior to irreversible structural damage. In support of our findings showing a relationship between oxygen metabolic stress and microstructural integrity, Fields et al 42 identified an association between oxygen metabolic stress and diminished functional connectivity in white matter unaffected by infarcts in children with SCD. In non-SCD sporadic small vessel disease, impairment in cerebrovascular reactivity, a metric of cerebral autoregulation, has been associated with disruption in microstructural integrity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We postulate that OEF may risk stratify microstructural impairment prior to irreversible structural damage. In support of our findings showing a relationship between oxygen metabolic stress and microstructural integrity, Fields et al 42 identified an association between oxygen metabolic stress and diminished functional connectivity in white matter unaffected by infarcts in children with SCD. In non-SCD sporadic small vessel disease, impairment in cerebrovascular reactivity, a metric of cerebral autoregulation, has been associated with disruption in microstructural integrity.…”
Section: Discussionsupporting
confidence: 91%
“…identified an association between oxygen metabolic stress and diminished functional connectivity in white matter unaffected by infarcts in children with SCD. 42 In non-SCD sporadic small vessel disease, impairment in cerebrovascular reactivity, a metric of cerebral autoregulation, has been associated with disruption in microstructural integrity. 43 Together, these studies contribute to the notion that inadequate oxygen delivery and elevation in oxygen metabolic stress may underlie the pathophysiology of microstructural disruption in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…The physiology of cerebral haemodynamics may explain alterations in cerebral StO 2 during exercise in SCA patients 12 . In SCA, individuals compensate for reduced arterial oxygen content by increasing cerebral blood flow and oxygen extraction 12,13 . Exhaustion of compensatory mechanisms may impact cerebral tissue oxygenation 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The ASE data were then decomposed into contributions from each tissue type (i.e., gray matter, white matter, CSF) 36 . The tissue‐specific ASE signal was independently processed to compute voxel‐wise OEF per participant 13 . A hematocrit value is required for OEF processing, and linear regression accounting for age and sex was used to estimate hematocrit for control participants with missing lab values.…”
Section: Methodsmentioning
confidence: 99%
“…OEF peaks within the border zone of the brain, where CBF nadirs 9,12 . Furthermore, the regions with a greatest increase in OEF align with regions of diminished functional connectivity 13 and greatest risk for infarction in patients with SCA 9,12 . Primary disease modification with an increase in arterial oxygen content via transfusion of hemoglobin A laden red blood cells relieves ongoing metabolic stress with a resultant decrease in cerebral blood flow and OEF in patients with SCA 11,14 …”
Section: Introductionmentioning
confidence: 98%